2005
DOI: 10.1177/154193120504902602
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Usability within a Virtual Reality Trainer for Medical Students

Abstract: Virtual reality (VR) offers the potential to train medical students on high-risk situations. The current study investigated VR training of medical students to diagnose and treat a patient avatar experiencing a serious head injury. The user interface was investigated, including use of tools, comfort and VR locomotion, and found to be sufficiently high to warrant training within a medical curriculum. In addition, actual learning as a function of VR training was assessed by comparing medical students' knowledge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…VR has also been used for training in the medical field. Ahlberg (19). The results revealed that identifying the object is easier when using tools in VR.…”
Section: Literature On Virtual Reality Applications For Training and Educationmentioning
confidence: 92%
See 1 more Smart Citation
“…VR has also been used for training in the medical field. Ahlberg (19). The results revealed that identifying the object is easier when using tools in VR.…”
Section: Literature On Virtual Reality Applications For Training and Educationmentioning
confidence: 92%
“…Nausea and motion sickness were reported in the literature when using VR for training (14,(18)(19)(20). Limiting the duration of the immersive experiment and taking short rests and breaks between experiments have been recommended.…”
Section: Immersive Virtual Realitymentioning
confidence: 99%